THE INFLUENCE OF COMPENSATION ON THE PERFORMANCE OF EMPLOYEES OF THE DEPARTMENT OF COOPERATIVES AND SMALL AND MEDIUM-SIZED ENTERPRISES (SMES) GOWA DISTRICT - Megawati Beddu; Rezky Nurbakti; Sitti Fadjriyah (Universitas Muhammadiyah Makassar, 2021)
The purpose of this research is to determine whether compensation has a significant effect on employee performance at the small and medium enterprise cooperative office of gowa regency, and how much influence the compensation and indicators have.(wages,salaries,incentives and benefits). Against the performance of and medium enterprise cooperative office in Gowa Regency. The method used in this research is quantitative method through questionnaires, observation and literature study. As well as distributing questionnaires to employees of the small and medium enterprise cooperative office in Gowa Regency. Total population 42 people. Through the Slovin formula, a sample of 42 respondents was selected. Data obtained by distributing questionnaire (Questionnaire). The data analysis technique used simple linear regression which had previously been analyzed using, validity test, reliability test, t test, classical assumption test and determination test (R2). The results of this study indicate that compensation has a positive and significant effect on employee performance at the small and medium enterprise cooperative office in Gowa Regency.